ANTECEDENTS IKATAN EMOSIONAL DAN MINAT PENGAMBILAN KREDIT ULANG PADA BANK BTPN COMAL - Habsari, Diyah (Master of Management Diponegoro University, 2013)
Bank BTPN Comal branch have decrese in amount of debitur each month from 2010 until 2012. Meanwhile, the importance of consumers’ growth in Indonesia banking and in BTPN MUR is the most important things. So the reseach problem is how to make an increase on debitur’s interest to re credit retrieval from BTPN MUR Comal branch.This research is purposed to analyze the effect of salesman competence toward emotional bounding, to analyze the effect of brand image toward emotional bounding, to analyze the effect of ease of payment toward emotional bounding, to analyze the effect of growth implementation toward emotional bounding, to analyze the effect of emotional bounding toward interest re credit retrieval.This research used primary data from the respondent and use the questionnaire that distributed to BTPB Comal branch consumers. Total od respondent are 125 participants. Technique analysis used are regression with classic assumption. From the result analysis we can know that data is normal, free from multicollinearity and heteroskedasticity so we can do the hypothesis testing (t test) to knowing the effect of independent variable toward dependent variable.The conclusion are: First, salesman competence affect emotional bonding. So the hypothesis accepted, where the affect of positive. Second, brand image affect the emotional bonding. Third, ease of payment affect the emotional bonding. Fourth, growth implementation affect emotional bonding. Last, the emotional bonding affect interest re credit retrieval.